Metodologia para detecção e correção de erros causados por radiação em computador de bordo de um CubeSat - PESTANA, Edeilson Pereira (2022)
The field of nanosatellites is constantly evolving and the demand for electronic components with levels of reliability adequate to the hostility of the space environment is growing. This generates an increasing need for systems capable of detecting and correcting errors induced by the effects of radiation on satellite memory elements. In this work, a method for detecting and correcting errors caused by radiation in a CubeSat onboard computer is proposed. The developed method uses the Hamming code algorithm together with the parity bit method, implemented in FPGA, to carry out the detection and correction of errors caused by events in the RAM memory of a microcontroller. The presented Scheme has the capacity to identify and correct errors of type SEU and detection of events of type DEU. The algorithm was simulated in software and at the end of the work a prototype of an on-board computer was developed where bench tests were performed. The developed method was compared to the classical Hamming code method to validate the results and gains.